EFFECT OF COMMUNITY BASED AREA-WIDE FRUIT FLY SUPPRESSION ON BACTROCERA DORSALIS POPULATION IN ORANGE ORCHARDS IN MUHEZA DISTRICT TANZANIA - Seguni, ZuberiSingano (International Journal of Research -GRANTHAALAYAH, 2016)
A community-based area wide fruit fly suppression exercise involving simultaneous application by farmers of methyl eugenol-mediated mass capture of males of Bactrocera dorsalis fruit fly, crop sanitation by burial of fallen fruits and SUCCESS bait (GF 121)spot application of citrus tree crowns, was undertaken in three villages in Muheza district, Tanga region north eastern Tanzania. Male fruit fly numbers in methyl eugenol traps dropped significantly following application of the treatments from 970 flies per trap per week before application of treatments in July 2011 to 100 and 46 flies six and nine months after treatments at Kwabada village; 200 flies per trap per week before to 34 and one flies after treatment at Kwemsaa village and from 800 flies before to 64 and 50 flies per trap per week during the same period at Mlingano village. However, a fall occurred also in untreated orchards indicating a possible spill-over effect of the treatments due to the large area covered. Moreover, the treated areas might have acted as a sink that drew fruit flies from neighbouring untreated orchards into it. The drastic fall in trapped males may be associated with the effect of the treatments in reducing the number of flies so that fewer were available to fly into the traps. The collective and simultaneous application by farmers of fruit fly suppression over a large crop area is a robust strategy to manage fruit flies in citrus and other fruits orchards such as mango. The results suggest that farmers can successfully implement area-wide fruit fly suppression in smallholder citrus systems.